FAM196B acts as oncogene and promotes proliferation of gastric cancer cells through AKT signaling pathway - Zhang, J.; Tong, D. D.; Xue, M.; Jiang, Q. Y.; Wang, X. F.; Yang, P. B.; Ni, L.; Zhao, L. Y.; Huang, C. (Cellular and Molecular Biology, 2017)
Gastric cancer (GC) is the second leading cause of cancer-related deaths worldwide, but the mechanisms remain unknown. Here we report that family with sequence similarity 196 member B (FAM196B) is highly expressed in primary GC tissues and the expression level is correlated with the clinicopathologic characteristics of GC. In this experiment, knockdown of FAM196B suppressed GC cell proliferation and induced G1/G0 to S phase cell cycle arrest by regulating Cyclin D1, Cyclin A and CDK2 expressions. Furthermore, we investigated the molecular mechanism of FAM196B action in GC. The results showed that knockdown of FAM196B inhibited the activation of AKT signaling pathway. We further revealed that activating of AKT rescued the effect of FAM196B knockdown on cell proliferation and drove cell re-enter into the S phase of the cell cycle with SC79 (a AKT activator). Our findings demonstrated that FAM196B may promote GC cell proliferation by activating AKT signaling pathway. Taken together, this study provides a new evidence that FAM196B functions as a novel oncogene and could be a potential therapeutic target in therapy of GC.